Integration of Battle Royale Games With Tabletop Games to Help Decision Making Skills - Febrianto, Nicholas Valentino; Nugroho, Agus Cahyo; Nugroho, Erdhi Widyarto (Soegijapranata Catholic University, 2024)
Effective decision-making skills are essential both in everyday life and in gaming contexts, where choices have major consequences. Board games, known for their strategic nature, provide an ideal platform to hone these skills. This research aims to understand decision-making skills using board games, using Rapid Application Development (RAD) methodology to collect data, implement updates, and improve the gaming experience. This project uses Unity to create applications that augment the gameplay. The result of this effort is a distinctive board game that differs from conventional table games, offering its players a new and exciting experience.